Spoilt for choice: Order routing decisions in fragmented equity markets - Peter Gomber; Satchit Sagade; Erik Theissen; Moritz Christian Weber; Christian Westheide (University of Cologne, Centre for Financial Research (CFR), 2016)
The equity trading landscape all over the world has changed dramatically in recent years. We have witnessed the advent of new trading venues and significant changes in the market shares of existing ones. We use an extensive panel dataset from the European equity markets to analyze the market shares of five categories of lit and dark trading mechanisms. Market design features, such as minimum tick size, immediacy and anonymity; market conditions, such as liquidity and volatility; and the informational environment have distinct implications for order routing decisions and trading venues' resulting market shares. Furthermore, these implications differ distinctly for small and large trades, probably because traders jointly optimize their trade size and venue choice. Our results both confirm and go beyond current theoretical predictions on trading in fragmented markets.
Keywords: G10; G12; 330; Dark Trading; Fragmentation; Anonymity; Immediacy